Back to content: Nelson Goodman as philosophical basis for multiliteracy - Pylkkö, Leena (Qualitative and Quantitative Methods in Libraries; Vol 3 No 4 (2014): December 2014 Issue, 2017)
Media and information literacy discussion needs a philosophical basis, which today is lacking. I propose that the thinking of Nelson Goodman be a fruitful basis.What is interesting in Goodman from the point of view of the libraries is his radical view on language. Language is for Goodman a way of making worlds. All arts: dance, music, pictures, and writing produce symbol systems and languages of their own. Understanding means taking part in the world of the artwork or text. The presentation also includes examples of everyday library work where the thought of world-creating helps understand the reading and media habits of different groups, especially those in need of special care, as people with different disabilities. When we look at the use of different media as a way of taking part in different worlds, and a making of worlds, this helps us in library work to develop a new view on customers even with disabilities as active world-makers.